Soft Tissue Response and Determination of Underlying Risk Drivers for Recession and Mucositis after AMSJI Implantation in the Maxilla - Van den Borre, Casper; De Neef, Björn; Loomans, Natalie A J; Rinaldi, Marco; Nout, Erik; Bouvry, Peter; Naert, Ignace; Van Stralen, Karlijn J; Mommaerts, Maurice Y (The International journal of oral and maxillofacial implants, 2024)
To evaluate the soft tissue response to the placement of additively manufactured subperiosteal jaw implants (AMSJI) in the severely atrophic maxilla and to identify possible risk factors for soft tissue breakdown. An international multicenter study was conducted, and 15 men (mean age: 64.62 years; SD: ± 6.75) and 25 women (mean age: 65.24 years; SD: ± 6.77) with advanced maxillary jaw resorption (Cawood and Howell Class V or more) were included in this study. General patient data were collected, and all subjects were clinically examined. Inclusion criteria were patients who underwent bilateral AMSJI placement in the maxilla at least 1 year prior. Exclusion criteria were patients who did not have patient, surgeon, or dentist consent to participate in the study before their inclusion. A total of 40 patients were enrolled, with a mean follow-up period of 917 days (SD: ± 306.89 days). Primary implant stability was achieved postoperatively in all cases, and all implants were loaded with a final prosthesis. At the time of the study, only 1 patient showed mobility (> 1 mm) of the bilateral AMSJI. Due to mucosal recession, exposure of the framework was seen in 26 patients (65%) and was mainly in the left (21.43% of 26) and right (18.57% of 26) midlateral region. A thin biotype and the presence of mucositis were found to be risk factors (P < .05). Although not significant, smokers had a risk of developing a recession that was nearly seven times (odds ratio: 6.88; P = .08) greater than that of nonsmokers. Twenty-six (65%) patients presented with a recession in one (or more) of the seven regions after oral rehabilitation with bilateral AMSJI placement. Several risk drivers were evaluated. The collapse of soft tissues around the AMSJI that led to caudal exposure of the arms was correlated with a thin biotype and the presence of mucositis.